2014
DOI: 10.1177/2054270414554049
|View full text |Cite
|
Sign up to set email alerts
|

Views of senior UK doctors about working in medicine: questionnaire survey

Abstract: SummaryObjectivesWe surveyed the UK medical qualifiers of 1993. We asked closed questions about their careers; and invited them to give us comments, if they wished, about any aspect of their work. Our aim in this paper is to report on the topics that this senior cohort of UK-trained doctors who work in UK medicine raised with us.DesignQuestionnaire surveyParticipants3479 contactable UK-trained medical graduates of 1993.SettingUK.Main outcome measuresComments made by doctors about their work, and their views ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It involves assessment of practice and of theoretical knowledge and can be examined through observation, written examination, interview and colleague/client feedback. Practitioner report also indicates the importance of practical experience in building the skills and knowledge of an expert practitioner (Lambert et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It involves assessment of practice and of theoretical knowledge and can be examined through observation, written examination, interview and colleague/client feedback. Practitioner report also indicates the importance of practical experience in building the skills and knowledge of an expert practitioner (Lambert et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It still is unclear what the special demands of female medical doctors and what are the implications on creating an accepted and more employee-orientated working environment in hospitals. The poor adaptation of working conditions in hospitals to demands and expectation of medical staff as already led to an increased level of part-time work ( 53 ), work-related stress ( 54 ), dissatisfaction with working hours, career perspectives and remuneration ( 55 ), and—finally—escape from curative activities ( 56 ). In summary, the gap between demand for top medical services and readily available capacities and competence of physicians is constantly widening.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Government agencies tasked with delivering public health services face the continuing challenge of retaining their staff in order to meet current and future targets [ 40 ]. As work-related stress correlates strongly with levels of job satisfaction and morale amongst staff [ 2 , 41 ], factors that ultimately influence staff retention rates [ 4 , 31 ], identifying ways to minimise stress and improve job satisfaction for new trainee doctors is critical [ 27 ]. This study has revealed that the provision of effective institutional support for new foundation doctors may promote increased job enjoyment and more positive attitudes towards work and thus could help safeguard the long-term retention of junior doctors.…”
Section: Discussionmentioning
confidence: 99%